Dampak Bullying Terhadap Kesehatan Mental Pada Siswa Sekolah Menegah Atas - Marista Fiana; Reni Muhka; Risnadhia Fiana; Sari Wulan Asih (LITERA ABDI: Jurnal Pengabdian Masyarakat, 2026)
ullying is an act in which someone hurts, insults, pressures, mentally undermines, and controls another person by using violence so that the victim receives all kinds of treatment carried out by the perpetrator. Bullying is an unwanted act, especially in a school environment. Bullying is behavior carried out by one or more people intentionally harming another person repeatedly. The purpose of this community service is to provide knowledge to students regarding an understanding of bullying behavior among students and to help students know how to avoid bullying at school. The method used in this Community Service activity is a lecture method that discusses material on the impact of bullying on mental health which is directly delivered by the resource person, as well as a question and answer session. The results of this socialization activity provide a clear picture that the issue of bullying among high school students still occurs. Many children do not understand that the behavior of teasing, pushing, ostracizing, or spreading rumors can be a form of hurtful bullying. Community service activities regarding the impact of bullying on mental health show that most students have a limited understanding of the forms of bullying and their consequences for mental health.